Dealing with complex issues : Networking, creative dialogue and a sense of audience in environmental management - Stubbs, Mark (Cranfield University, 1998)
In recent years organisational decision-makers have been portrayed within the'Media,, and academic literature, as struggling to deal with complex, transboundary issues. Such issues typically involve interactions between social and natural processes which produce effects distant in time and space from their recognised cause, with pertinent processes transcending the boundaries of interest and authority associated with any single organisation. In these situations, debate about the significance of phenomena, and about who should respond, is often intense with consensus apparently limited to the belief that not enough is known. Using the arena of environmental management as its central example, this thesis argues that those who consider themselves part of the process of dealing with such complexity should seek to be guided by an acute `sense of audience'. This call for reflexivity - continually modifying one's behaviour in response to an emerging appreciation of how others interpret a dynamic situation in which one is actively engaged - is demonstrated in both the content and structure of the research presented in support of the thesis. Through an adaptive research process characterised by continual movement between the field and relevant literatures, the `sense of audience' thesis is joined by emergent concepts of `networking' and `creative dialogue'. These provide practical guidance on how pertinent perspectives can be brought together to discern desirable and feasible interventions on complex issues. Grounded in insights gained through participative research with organisational actors attempting to develop integrated approaches to environmental management in a range of settings, these emergent concepts are interwoven with aspects of the contexts that inspired them, to produce a `constituitive process theory' of the formation of `adaptive response networks'. This theory shows how networks can form across organisations when diverse stakeholders are encouraged to share their concerns, data and expertise about complex, transboundary issues.